A role of mulberry leaves in improving resistance to virus‐mediated disease in Allomyrina dichotoma. Issue 2 (17th January 2020) - Kwak, Kyu‐Won; Han, Myung‐Sae; Kim, Sun Young; Kim, Eunsun; Kim, Nang‐Hee; Park, Kwanho; Kim, Yong‐Soon; Lee, Heui‐Sam
Abstract: The purpose of this study was to develop a safe and effective method for preventing Allomyrina dichotoma nudivirus ( AdNV ) infection in the Korean horned beetle, Allomyrina dichotoma, found on the farms in the Republic of Korea. Mulberry leaf powder was added to fermented oak sawdust to minimize mortality in AdNV ‐infected A. dichotoma . Mulberry leaves were found to contain 1‐deoxynojirimycin, which has anti‐inflammatory, antiviral, and anti‐tumor effects. Based on the proposed antiviral effects of mulberry leaves, a feed of fermented sawdust combined with 1% or 5% mulberry leaf powder was fed to AdNV ‐infected second or third stage A. dichotoma larvae. The larval mortality rate was recorded over 10 weeks. The second and third instar larvae that were fed with the sawdust mixture with 5% mulberry leaf powder had mortality rates of 60% and 30%, respectively. In contrast, the control group that was fed with the sawdust without mulberry leaf powder had a mortality rate of 100%. Also, we confirmed that AdNV was not detected in the experimental group that was subjected to an outdoor application test for 8 months with mulberry leaf powder treatment. A reduced mortality rate after treatment with 1% mulberry leaf powder was observed in the field application. In addition, a comparison of the control colony and mulberry leaf treated group showed a statistical difference in growth of larvae at various states, and demonstrated the efficiency of mulberry leaf powder combined with fermented sawdust for treatment of AdNV‐ infected A. dichotoma .